Growth of Kaffir Lime (Citrus hystrix DC) Cell Line Derived from Seed Explant After Yeast Elicitation Using Pure and Technical Grade Yeast - Dewi Yuliana Rizqi; Frisca Damayanti; Fhea Putri Cristy; Alisa Julia Nurulita; Aries Bagus Sasongko; Endang Semiarti; Woro Anindito Sri Tunjung (Universitas Gadjah Mada, 2022)
The addition of elicitors in kaffir lime (Citrus hystrix DC.) culture is one of strategies for obtaining and increasing the production of secondary metabolites. Saccharomyces cerevisiae is one of the elicitors that can be used to increase secondary metabolites such as terpenoids. However, in its use, the pure cultures of S. cerevisiae are expensive. Therefore, the first objective of this study was to analyze the ability of technical grade (commercial baker’s yeast) to be used as an elicitor and measure the growth of kaffir lime cell line after being elicited by pure and technical grade (commercial baker’s yeast). The second objective is to determine the best time to subculture kaffir lime cell line after elicitation. We observed the morphology and measured the growth curve of pure and technical grade yeast until the 4th subculture generation. Furthermore, we used both grades of yeast for elicitation. Kaffir lime cell suspension was treated with 10 ppm pure grade or 5 ppm and 10 ppm technical grade yeast for 4 days. After elicitation, kaffir lime cell lines were subcultured and their growth was analyzed. The result showed that the morphology and growth curve of technical grade until 4th subculture generations was similar to the pure grade. On the other hand, after elicitation using pure and technical grade yeast and being subcultured, the growth of the elicitated kaffir lime cell line had the same pattern as the control group, but the cell density of the control group was higher than the elicitated group. The initial stationary phase of kaffir lime cell line was on the 17th day which is the best time to subculture. The subculturing process is important to maintain the viability of the kaffir lime cell line.